Teachers’ informed decision-making in evaluation: Corollary of ELT curriculum as a human lived experience - Quintero Polo, Álvaro Hernán (Colombian Applied Linguistics Journal, 2003)
This article characterizes informed decision-making as one important activity of evaluation in the English Language Teaching (ELT) curriculum. I emphasize on a distinction between human and technical approaches to evaluation. This emphasis is consequence of my reflection upon my and some in-service teachers’ perceptions about literature and small-scale research projects related to the area of evaluation. In this article, I also intend to contribute to an understanding of why educational processes need to be seen as a lived experience for which informed decision-making can be used as a sound practice in a process of evaluation. A practical academic experience illustrates the discussions in this article. I led the practical experience as a professor of a seminar on testing and evaluation in English language teaching (ELT), in the Master’s Program in Applied Linguistics to the Teaching of English as a Foreign Language at the Distrital University in Bogotá, Colombia.